Transforming Turkish electricity system in the context of circular economy and green deal: impacts on steel and agricultural production - KURŞUN, BERRİN (My University, 2024)
Two important but conflicting goals in Turkey’s energy policy have been ensuring energy security through increased indigenous energy resource utilization and meeting the 2053 net zero emission commitment. Based on this, this work explores emission mitigation pathways for Turkey’s electricity system through circularity approaches of CO2 utilization and framework material recycling (FMR). Using mathematical models, eight life cycle impact potentials are evaluated including global warming potential (GWP). The extended impact on steel and agricultural production was also examined in the Green Deal context. The circularity approaches investigated showed that the GWP of Turkey’s wind, solar, and lignite energy sources reduce from the base values of 7.3 gCO2eq./kWh, 29.5 gCO2eq./kWh and 1130 gCO2eq./kWh to 2.72 gCO2eq./kWh, 21.08 gCO2eq./kWh and 241.26 gCO2eq./kWh, respectively. Fifty percent recycling ratio is also determined as the optimum for CO2 utilization and FMR. With this ratio, 21.84% CO2 emission reduction corresponding to 0.083 GT annual CO2 savings is achieved in the Turkish electricity mix. The decarbonization of electricity results in 25.0% and 27.0% GWP impact reductions in the agricultural and steel sectors, respectively. Hence, the decarbonization of electricity mix can significantly ease the negative impacts of the Green Deal on Turkey’s economy. Additionally, promoting and increasing the share of renewable energy sources in the electricity mix can further enhance these environmental benefits.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Fizik; Nükleer Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Physics; Nuclear physics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; ENERJİ VE YAKITLAR; NÜKLEER BİLİMİ VE TEKNOLOJİSİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ENERGY & FUELS; NUCLEAR SCIENCE & TECHNOLOGY; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Nükleer Enerji ve Mühendislik; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Renewable Energy, Sustainability and the Environment; Physical Sciences; Nuclear Energy and Engineering; Fuel Technology; Energy Engineering and Power Technology; CO2 utilization; Electricity mix decarbonization; framework material recycling; Green Deal; lifecycle environmental impacts